Habitual Physical Activity, Sedentary Behaviour and Bone Health in Rheumatoid Arthritis - Prioreschi, A.; Makda, M.; Tikly, M.; McVeigh, Joanne (2015)
Associations between habitual physical activity levels and bone health in rheumatoid arthritis (RA) were assessed. Twenty nine female patients with RA were assessed for bone mineral density (BMD), and classified as having low or normal hip BMD. Habitual physical activity levels were assessed using accelerometry, and disease activity was assessed using the Clinical Disease Activity Index (CDAI). Twenty one patients had normal bone mass, while 8 had low bone mass. There was no difference in age in the normal bone mass group (51(8)) compared to the low bone mass group (57(12)), p=0.19. Patients with normal bone mass spent on average 2 h less per day in sedentary activity (65(4)% vs. 73(2)%, p<0.01), over 70 min more time in light activity (23(1)% vs. 18(2)%, p<0.01), and over 50 min more in moderate activity per day (12(3)% vs. 8(2)%, p<0.01) than did patients with low bone mass, independently of disease activity or duration. Patients with normal bone mass broke up their sedentary time more frequently per day (72(21) vs. 53(18) times per day, p=0.03). The results of this study indicate that higher habitual activity levels may be protective of bone health in patients with RA, and should be encouraged.